2005
DOI: 10.1016/j.actamat.2005.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Laser annealing of amorphous NiTi shape memory alloy thin films to locally induce shape memory properties

Abstract: We present the results of a crystallization study on NiTi shape memory thin films in which amorphous films are annealed by a scanning laser. This technique has the advantage that shape memory properties can be spatially distributed as required by the application. A kinetics study shows that nucleation of the crystalline phase occurs homogenously in the films. Consequently, the laser annealing process produces polycrystalline films with a random crystallographic texture.The crystallized films have a uniform mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(41 citation statements)
references
References 21 publications
(27 reference statements)
0
37
0
Order By: Relevance
“…fabrication and performance. For fabrication, similar actuators could be reduced to millimeter feature sizes (26) using current methods or submillimeter scales using physical vapor deposition and patterning (27). For these actuator types, Joule heating becomes more effective at smaller scales, bandwidth will increase (mechanically as well as thermodynamically), and the energy density should remain constant.…”
Section: Discussionmentioning
confidence: 99%
“…fabrication and performance. For fabrication, similar actuators could be reduced to millimeter feature sizes (26) using current methods or submillimeter scales using physical vapor deposition and patterning (27). For these actuator types, Joule heating becomes more effective at smaller scales, bandwidth will increase (mechanically as well as thermodynamically), and the energy density should remain constant.…”
Section: Discussionmentioning
confidence: 99%
“…On closer observation, these grains had thin alternating bands of white and dark contrast that are caused by the (0 0 1) compound twins of B19', as reported by Waitz et al [34] Additional reports on the twin martensitic structure in a Ni-Ti thin film suggests that these are <011> type II twins, which are observed frequently in bulk material, furnace, and laser annealed NiTi thin films. [35,36] The <011> type II twins band is much narrower because of the much smaller grain size in a thin film. Zhang et al [35] reported that in a Ti-Ni thin film the existence of <011> type II twinning is a consequence of lattice invariant shear in the cubic to monoclinic transformation.…”
Section: Microstructural Analysismentioning
confidence: 99%
“…It exhibits SE while the test temperature is close to the austenite finish temperature (A f ) [8][9][10][11][12][13][14]. A considerable body of experiments has been conducted on NiTi alloys to investigate its strain rate and temperature-dependent phase transformation behaviour [11,12,[14][15][16][17][18][19]. Nemat-Nasser et al [8,9] studied the dynamic behaviour of NiTi at various strain rates in a range of 10 −3 to about 2 × 10 4 s −1 and at temperatures in a range of 77-400 K. The results showed that the SE behaviour of NiTi was more sensitive to temperature than to strain rate.…”
Section: Introductionmentioning
confidence: 99%